KOMPETENSI PENGETAHUAN PASAR DALAM MENDUKUNG KEUNGGULAN PRODUK UNTUK MENINGKATKAN KINERJA PEMASARAN: STUDI KASUS PADA PT ANEKA GAS INDUSTRI SALES REGION JAWA TENGAH TAHUN 2015 - Prasetyo, Ageng (PRIMA EKONOMIKA, 2018)
This study focus on how the company need to know about the market expectation beforethe product was launched esspecially in PT Aneka Gas Industri Sales Region Jawa Tengah in2015.The ability of the company to know the market was called the market knowledgecompetence. Its concist of three major aspects such as customer knowledge competence,competitor knowledge competence and the interface between R&D with marketingdepartment. The higher market knowledge competence was predicted can creates the higherthe competitive advantage in the market place. And as the result the competitive advantagecan increase the marketing performance, these was inluded sales volume, sales growth andcustomers growth. Populations of this study were 100 customers of PT Aneka Gas IndustriSales Region Jawa Tengah, and the samples of this study were 20 customers which devidedinto 2 categories of monthly purchases amount. We expected this study could be applied inthe company in order to support policies and strategies in the marketing field mainly ondeveloping new products.